Methylation of the Sf locus in almond is associated with S-RNase loss of function - Fernández i Martí A.; Gradziel T.M.; Socias i Company R. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
Self-compatibility in almond (Prunus amygdalus Batsch) is attributed to the presence of the Sf haplotype, allelic to and dominant over the series of S-alleles controlling self-incompatibility. Some forms of the Sf haplotype, however, are phenotypically self-incompatible even though their nucleotide sequences are identical. DNA from leaves and styles from genetically diverse almond samples was cloned and sequenced and then analyzed for changes affecting Sf variants. Epigenetic changes in several cytosine residues were detected in a fragment of 4700 bp of the 5’ upstream region of all self-compatible samples of the Sf allele, differentiating them from all self-incompatible samples of Sf analyzed. This is the first report of DNA methylation in a Rosaceae species and appears to be strongly associated with inactivation of the Sf allele.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)